BRICS : emergência dos arranjos informais - Farias, Carlos Eduardo dos Santos (2015)
This research paper proposes an analysis of the emergence of informal arrangements as a new form of multilateralism, pointing out the historical evolution of international organizations as institutions representing multilateralism in practice. The crisis in classical multilateralism is unequivocal, for the world has been conferring a new shape to international relationships among its actors: less bureaucratic, less institutionalized, more efficient and effective. Informal arrangements bring in themselves cooperation as element of order, leaving the idea of ¿power for power¿ behind, in which the rich exploited the poor in compliance with military forces. BRICS is an example of a successful informal arrangement, that puts together such different countries with an only purpose in mind: development of participants based on the idea of cooperation. Times have changed, and international relationships must now adapt to this new world order.